Amino Acid Sensor Kinase Gcn2 Is Required for Conidiation, Secondary Metabolism, and Cell Wall Integrity in the Taxol-Producer Pestalotiopsis microspora - Wang, Dan; Akhberdi, Oren; Hao, Xiaoran; Yu, Xi; Chen, Longfei; Liu, Yanjie; Zhu, Xudong (Frontiers in Microbiology, 2017)
The canonical Gcn2/Cpc1 kinase in fungi coordinates the expression of target genes in response to amino acid starvation. To investigate its possible role in secondary metabolism, we characterized a gcn2 homolog in the taxol-producing fungus Pestalotiopsis microspora. Deletion of the gene led to severe physiological defects under amino acid starvation, suggesting a conserved function of gcn2 in amino acid sensing. The mutant strain △gcn2 displayed retardation in vegetative growth. It generated dramatically fewer conidia, suggesting a connection between amino acid metabolism and conidiation in this fungus. Importantly, disruption of the gene altered the production of secondary metabolites by HPLC profiling. For instance, under amino acid starvation, the deletion strain △gcn2 barely produced secondary metabolites including the known natural product pestalotiollide B. Even more, we showed that gcn2 played critical roles in the tolerance to several stress conditions. △gcn2 exhibited a hypersensitivity to Calcofluor white and Congo red, implying a role of Gcn2 in maintaining the integrity of the cell wall. This study suggests that Gcn2 kinase is an important global regulator in the growth and development of filamentous fungi and will provide knowledge for the manipulation of secondary metabolism in P. microspora.